Estimasi Stok Karbon pada Biomassa Lamun di Pulau Semak Daun, Kepulauan Seribu - Jessica V. Gunawan; Maxi Parengkuan; A’an J. Wahyudi; Firman Zulpikar (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Carbon Stock Estimation in Seagrass Biomass on Semak Daun Island, Thousand Islands. Seagrass ecosystem has a vital role in protecting the coastal ecosystem. It can also sequester and store carbon as an organic material (blue carbon) for a long time. However, anthropogenic activities in coastal areas give environmental stress on the seagrass ecosystem. This research was conducted to assess the carbon stock of seagrass biomass in Semak Daun Island in order to evaluate the potential of the seagrass meadows in sequestering carbon. Sampling and observation were held in the seagrass ecosystem to obtain seagrass density, biomass, frequency of occurrence, water quality, and anthropogenic activity. Carbon stock was calculated by the loss of ignition (LOI) method, and combined with density to determine the total carbon stock in the whole area of seagrass meadows. Seagrass species in Semak Daun Island consist of Halophila ovalis, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, and Halodule uninervis. The coverage area of seagrass in Semak Daun Island was 9.1 ha with carbon stock value of 1.84 ton C or equivalent to 6.76 ton CO2. Fifty two percent of the carbon stock was originated from the below-ground biomass and 48% from the above-ground biomass.